¿Qué pasa con las ciencias sociales en la construcción del proyecto político de la interculturalidad? - González, Laura (2025)
The implementation of interculturalism is difficult at the educational level, given the Western roots of the academic world. The objective of this work was to analyze the role of the social sciences, disciplines originating from a Eurocentric world, in the construction of this political project. The methodology used is qualitative. For the analysis, three cases from professional practice were selected in which social scientists encountered information that does not fit the canons of scientificity. A discursive analysis of the cases was conducted. The result was the need for researchers to convert primary information to fit the dominant parameters. It was concluded that there are constant power mechanisms in the practice of dealing with information that is not anthropocentric, objective, or materialistic, generating significant limitations for the construction of interculturalism.